The wars of the 1860s and the economic recovery of the province of Bahia - Vaz Sampaio, Marcos Guedes (Revista Crítica Histórica, 2020)
The economy of the Province of Bahia faced a recessive period between the years 1857 and 1860 due to three predominant factors, the prolonged drought that dragged on for four years, the US crisis of 1857, which spread its damaging effects on the international system and the monetary policy of the imperial government that ranged from pluriemissionism to centralization in the Bank of Brazil, culminating in the crisis of 1859-1860. After a significant decline in domestic economic performance, the trade balance showed a substantial recovery following the outbreak of the United States War of Independence (1861-1865), prolonging this auspicious moment with the advent of the Paraguayan War (1864-1870). The troubled belligerent years have had positive effects on local cultures, especially sugar, cotton and tobacco, revealing the important dependence of an exogenous factor to lead the internal burial in the face of a fragile domestic market of low monetarization, high concentration of income and little diversified productive structure.